Allogeneic stem cell transplantation in patients with myelofibrosis harboring the MPL mutation. (16th September 2019) - Mannina, Daniele; Gagelmann, Nico; Badbaran, Anita; Ditschkowski, Markus; Bogdanov, Rashit; Robin, Marie; Cassinat, Bruno; Heuser, Michael; Shahswar, Rabia; Thol, Felicitas; Beelen, Dietrich; Kröger, Nicolaus
Abstract: Introduction: Primary and post‐ET/PV myelofibrosis are myeloproliferative neoplasms harboring in most cases driving mutations in JAK2, CALR or MPL, and a variable number of additional mutations in other genes. Molecular analysis represents a powerful tool to guide prognosis and clinical management. Only about 10% of patients with myelofibrosis harbor alterations in MPL gene. No data are available about the transplantation outcome in the specific MPL ‐mutated group. Patients: We collected the data of 18 myelofibrosis patients(primary: 14; post‐ET: 4) transplanted in 4 EBMT centers (Hamburg, Paris, Essen, and Hannover) between 2005 and 2016. Results: Before the transplant, we explored the molecular profile by NGS and reported the frequency of mutations occurring in a panel of genes including JAK2, MPL, CALR, U2AF1, SRSF2, SF3B1, ASXL1, IDH1, IDH2, CBL, DNMT3A, TET2, EZH2, TP53, IKZF1, NRAS, KRAS, FLT3, SH2B3, and RUNX1 . The 1‐year transplant‐related mortality was 16.5%, 5‐years overall survival and 5‐y relapse‐free survival 83.5%. The only relapse occurred in a patient who harbored mutations in both ASXL1 and EZH2 genes. Conclusion: These retrospective data suggest that MPL‐mutated myelofibrosis patients have a favorable outcome after allogeneic transplantation with very low rate of disease relapse (5.5%) in comparison with the available historical controls regarding myelofibrosis in all.